Relationship between Teacher Academic Qualification with Learning Management in Early Childhood - Wulandari, Tika (Muhammadiyah University Prss, 2020)
Research on the Influence Motivation Study and Environmental Learning Against Achievement Learning Students showed that There is the influence of positive motivation to learn and environmental learn to achievement learn student . case is shown by the analysis of regression linear multiple , that the value of t count motivation to learn at 2.476 with significance 0.016 0.05 then H0 is accepted , and environmental learning has value t arithmetic amounted to 4.977 with significance 0.000 0.05 then H0 is accepted . While the value of F arithmetic amounted to 53.069, and the value of R square of 0.639 (63.9%). Relative contribution to the variable of learning motivation give a donation of 31% and variable environment study provides donations relatively amounted to 69%, the total contribution relative of 100%. Donations effective at variable motivation to learn by 19.81% and environment study by 63.91%, which means that the motivation to learn and environment study are jointly provide donations effectively amounted to 63.91% against the achievement of learning , and 36.09% of other variables not examined .